2014
DOI: 10.1051/0004-6361/201423400
|View full text |Cite
|
Sign up to set email alerts
|

The Penn State − Toruń Centre for Astronomy Planet Search stars

Abstract: Context. Standard stellar evolution theory does not predict existence of Li-rich giant stars. Several mechanisms for Li-enrichment have been proposed to operate at certain locations inside some stars. The actual mechanism operating in real stars is still unknown. Aims. Using the sample of 348 stars from the Penn State − Toruń Centre for Astronomy Planet Search, for which uniformly determined atmospheric parameters are available, with chemical abundances and rotational velocities presented here, we investigate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
78
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(87 citation statements)
references
References 70 publications
9
78
0
Order By: Relevance
“…We also found that TYC 3930-01790-1 and three out of 16 stars with incomplete data in Zieliński et al (2012): TYC 0405-01700-1, TYC 3226-01083-1, TYC 3318-00020-1 are fast rotators with weak and variable CCF (see Fig. 1), which is in good agreement with the results of Adamów et al (2014) for the last three objects. All other stars presented in Zieliński et al (2012) show stable single CCF, which makes them either single or SB1.…”
Section: Cross-correlation Function Analysissupporting
confidence: 89%
“…We also found that TYC 3930-01790-1 and three out of 16 stars with incomplete data in Zieliński et al (2012): TYC 0405-01700-1, TYC 3226-01083-1, TYC 3318-00020-1 are fast rotators with weak and variable CCF (see Fig. 1), which is in good agreement with the results of Adamów et al (2014) for the last three objects. All other stars presented in Zieliński et al (2012) show stable single CCF, which makes them either single or SB1.…”
Section: Cross-correlation Function Analysissupporting
confidence: 89%
“…127 hosts a brown dwarf of 19.8 M J at a distance of 2.4 AU with a period of 678 days (LM07). One can then speculate that a possible explanation for the enhanced Li observed in this star is the engulfment of a putative short-period planet that previously existed in the system as might be the case of other Li-rich planet hosts presented in Adamów et al (2012Adamów et al ( , 2014.…”
Section: Ngc 4349 No 127mentioning
confidence: 86%
“…Also, several studies (Gonzalez et al 2009;Monaco et al 2011;Lebzelter et al 2012;Ruchti et al 2011;Martell & Shetrone 2013;Adamow et al 2014) report that some giants with large Li enhancement are occupied between the bump and tip of the RGB. It would be a worthwhile exercise to differentiate RGB stars from the early asymptotic giant branch (AGB) stars.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, one ought to be cautious about associating Li-enhancement in K giants with the mass-loss events or vice versa. Also, assuming the possibility that planet engulfment enriches host-star Li abundance, hence IR excess (see Denissenkov & Herwig 2004;Carlberg et al 2010;Adamow et al 2014), and that the engulfment may happen anywhere along the RGB, one would expect Li enhancement across the RGB but not necessarily at the narrow bump luminosity. Absence of K giants with Li enhancement below and above the bump region casts shadow on the external origin scenario.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation